Aftereffects of Spectrally Similar and Dissimilar Spectral Motion Adaptors in the Tritone Paradox - Malek, Stephanie; Sperschneider, Konrad (Frontiers in Psychology, 2018)
Shepard tones consist of octave-spaced components, whose amplitudes are generated under a fixed bell-shaped spectral envelope. They are well defined in pitch chroma, but generate octave confusions that in turn can produce ambiguities in the perceived relative pitch heights when their chromas are exactly a tritone apart (the tritone paradox). This study examined the effects of tonal context on relative pitch height judgments using adaptor sequences followed by target sequences (pairs of Shepard tones of different chromas separated by a tritone). Listeners judged whether the second target Shepard tone was higher or lower than the first. Adaptor sequences consisted of rising or falling scales (43 s at the beginning of each block, 4 s before each target sequence). Two sets of Shepard tones were used for adaptors and targets that were generated under spectral envelopes centered at either A3 (220 Hz) and C6 (1046 Hz). Pitch direction judgments (rising vs. falling) to spectrally consistent (A3-A3, C6-C6) and inconsistent (A3-C6, C6-A3) adaptor-target combinations were studied. Large significant contrastive aftereffects (0.08-0.21 change in fraction of pitch direction responses) were only found for the Shepard tones that were judged as high in the control condition (judgments about the target sequences without adaptor sequences) for the consistent adaptor-target conditions (A3-A3, C6-C6). The experiments rule out explanations based on non-sensory decision making processes. Possible explanations in terms of perceptual aftereffects caused by adaptation in central auditory frequency-motion detectors are discussed.